Extrapulmonary tuberculosis in patients with RET fusion-positive non-small cell lung cancer treated with pralsetinib: A Korean single-centre compassionate use experience. (December 2021) - Lee, Yong-Pyo; Jeong, Byeong-Ho; Eun, Yeonghee; Kang, Cheol-In; Park, Sehhoon; Jung, Hyun Ae; Lee, Se-Hoon; Ahn, Jin Seok; Ahn, Myung-Ju; Park, Keunchil; Sun, Jong-Mu
Abstract: Background: Pralsetinib, an RET inhibitor, has shown a dramatic response in patients with RET fusion- or mutation-positive tumours in previous studies. As a novel target agent, however, the safety of pralsetinib remains to be determined. Herein, we present two cases of extrapulmonary tuberculosis (TB) that developed during pralsetinib therapy. Methods: From April 2020, we administered pralsetinib to a total of 10 patients with RET fusion-positive non-small cell lung cancer under the compassionate use program. We retrospectively analysed the clinical efficacy of and adverse events related to pralsetinib therapy. Results: Of the nine patients with measurable lesions, seven achieved a partial response. Additionally, one patient without measurable lesions also showed a clinical response. As of January 8, 2021, nine patients were still receiving pralsetinib therapy, while only one had discontinued pralsetinib therapy. Most adverse events were mild and manageable. However, two patients experienced extrapulmonary TB shortly after starting pralsetinib. The disease was well controlled with anti-TB medication, and the cancer lesions were managed through ongoing pralsetinib therapy. Conclusion: The development of TB during pralsetinib therapy is worth noting, although further large studies are required to demonstrate definitive relationship between causality and underlying mechanism. Highlights: Patients with RET-positive cancer had profound benefits from pralsetinib therapy. Pralsetinib also inhibits JAK1, which is important in immune surveillance. We should be aware of possible tuberculosis infection during pralsetinib therapy.